Educational leadership model: an Islamic perspective - Salleh, Mohamad Johdi (International Islamic University Malaysia, 2018)
This paper discusses a model of leadership from an Islamic perspective. Drawn from a concatenation of authentic Islamic texts and sources, the model comprises ten principles synopsized simply as L-E-A-D-E-R-S-H-I-P with each letter illustrating a principle of good governance. The principles were derived from a thorough examination and analysis of various sources that included the Qur’an, prophetic traditions, biographies of the Prophet's companions, thoughts of classical and contemporary scholars, and best practices in Islamic leadership. In essence, the model proposes that a leader should lead like an imam in prayers, educate and be educated, communicate explicit organisational aims and vision, use effective delivery strategies, empower those under him rather than keeping all power to himself, and lead in piety with justice, integrity and humility. The model is comprehensive--offered as a solution to guide the leadership and management practices of educational institutions in the Muslim world. The application of the model and adherence to its principles should help to develop Muslim leaders’ competencies, promote organisational transformation among Muslim institutions, and forge greater solidarity within their working communities.